Fat Grafting for Hand Rejuvenation - Conlon, Christopher J.; Abu-Ghname, Amjed; Davis, Matthew J.; Ali, Kausar; Winocour, Sebastian J.; Eisemann, Michael L.; Winocour, Julian (Seminars in Plastic Surgery, 2020)
The hands are one of the most visible parts of the body, and prominent dorsal veins and extensor tendons are the most readily recognized signs of the aging process. Fat grafting has been demonstrated to be a safe and effective method of hand rejuvenation by restoration of subcutaneous fat. Despite some variability in the technical approach, fat grafting techniques are consistent in their use of low-pressure injection with standard cannula sizes, small aliquots of graft, and a total volume of graft greater than or equal to 15 mL per hand. While distribution of the fat is an area of debate and a topic of active research, published studies have shown high patient satisfaction rates, suggesting that perhaps the restoration of volume alone is paramount. In this article, we will review the applications of fat grafting to the hand, focusing primarily on its role in hand rejuvenation.
Keywords: fat grafting; lipofilling; autologous fat transfer; hand rejuvenation